Assessing Psychological Well-being in TVET Stakeholders: Implications for Sustainable Workforce Development - Azizan, Norazizah; Omar, Anis Fathirah; Muhamad Yusof, Muhamad Ashman; Mehat, Nur Diana; Hamidi, Saidatul Rahah (Journal of Technical Education and Training, 2024)
The psychological well-being of the community is crucial for sustaining a productive and effective workforce. However, there is limited research on integrating well-being into Technical and Vocational Education and Training (TVET) strategies to improve community well-being, specifically psychological and mental health. The purpose of this study is to assess psychological well-being across five domains: positive emotions, negative emotions, life satisfaction, psychological functioning, and social well-being, besides to emphasizing wellbeing and TVET sustainability. Data were collected from 3062 civil officials in the Ministry of Rural and Regional Development (KKDW) by using random sampling methods, using the Malaysian Psychological Well-being Index (IKPM). Findings reveal a moderate level of composite index of psychological well-being among civil servants that includes policymakers and instructors of TVET. These results underscore the need for specific interventions to enhance civil servants' well-being. Improving the psychological well-being index can aid in designing and managing TVET programs, leading to better educational outcomes and workforce development. Implementing personalized programs targeting various well-being areas could significantly improve mental health, fostering a more supportive and productive work environment. Additionally, developing detailed civil servant profiles to identify individuals or groups needing precise psychological interventions is planned. Integrating well-being into TVET initiatives can further enhance psychological well-being by equipping TVET stakeholders with the necessary skills and knowledge to perform their roles effectively, thereby increasing job satisfaction and reducing stress levels. These findings highlight the importance of targeted interventions to improve the overall well-being of TVET for sustainable growth.